Exome sequencing identifies PD‐L2 as a potential predisposition gene for lymphoma. Issue 3 (29th May 2022) - Shao, Jianming; Gao, Lei; Leung, Marco L.; Gallinger, Bailey; Inglese, Cara; Meyn, M. Stephen; Del Gaudio, Daniela; Das, Soma; Li, Zejuan
Abstract: To investigate germline predisposition in lymphoma, we performed whole‐exome sequencing and discovered a novel variant (c.817‐1G>T) in programmed cell death 1 ligand 2 ( PD‐L2 ) in a family with early‐onset lymphomas and other cancers. The variant was present in the proband with follicular lymphoma and his son with Hodgkin's lymphoma. It was in the terminal splice acceptor site of PD‐L2 and embedded in a putative enhancer of Janus kinase 2 ( JAK2 ) and programmed cell death 1 ligand ( PD‐L1 ). We also found that gene expression of PD‐L2, PD‐L1, and JAK2 was significantly increased. Using 3′ rapid amplification of cDNA ends (3′ RACE), we detected an abnormal PD‐L2 transcript in the son. Thus, the c.817‐1G>T variant may result in the elevated PD‐L2 expression due to the abnormal PD‐L2 transcript and the elevated PD‐L1 and JAK2 expression due to increased enhancer activity of PD‐L1 and JAK2 . The PD‐L2 novel variant likely underlies the genetic etiology of the lymphomas in the family. As PD‐L2 plays critical roles in tumor immunity, identification of PD‐L2 as a germline predisposition gene may inform personalized immunotherapy in lymphoma patients.